Peripheral inflammation as a potential mechanism and preventive strategy for perioperative neurocognitive disorder under general anesthesia and surgery - Li, Yuan; Li, Ying-Jie; Fang, Xu; Chen, Dong-Qin; Yu, Wan-Qiu; Zhu, Zhao-Qiong (Frontiers in Cellular Neuroscience, 2024)
General anesthesia, as a commonly used medical intervention, has been widely applied during surgical procedures to ensure rapid loss of consciousness and pain relief for patients. However, recent research suggests that general anesthesia may be associated with the occurrence of perioperative neurocognitive disorder (PND). PND is characterized by a decline in cognitive function after surgery, including impairments in attention, memory, learning, and executive functions. With the increasing trend of population aging, the burden of PND on patients and society's health and economy is becoming more evident. Currently, the clinical consensus tends to believe that peripheral inflammation is involved in the pathogenesis of PND, providing strong support for further investigating the mechanisms and prevention of PND.